ONLINE LEARNING STRATEGIES BASED ON TEACHERS AND PARENTS COLLABORATION DURING THE COVID-19 PANDEMIC (Jurusan PGPAUD FIP UNNES, 2022)
This study aims to: 1) Explain online learning strategies based on collaboration between teachers and parents during the Covid-19 pandemic at the Nusa Indah Kangkung PAUD Post, Kendal Regency. 2) Explaining the challenges of implementing online learning based on collaboration between teachers and parents during the Covid-19 Pandemic at the Nusa Indah Kangkung PAUD Post, Kendal Regency. The method used in this research is descriptive qualitative research method. The time required is 4 months, namely January 2021 to May 2021. Data triangulation techniques are used to obtain valid data by comparing one data to another. Data was collected through interview, observation, and documentation techniques. Observations were made to find out online learning strategies based on collaboration between teachers and parents of PAUD school students. The research subjects were one school principal, one teacher and two parents of the Nusa Indah Kangkung Post PAUD students. The results of the research conducted by researchers are as follows: 1). The constructivist pedagogical strategy is a strategy used in online learning during the Covid-19 pandemic at the Nusa Indah Kangkung PAUD Post, this strategy includes collaboration, projects, questions and discussions. 2). The main challenges faced by teachers and parents when collaborating in the implementation of online learning are network limitations, lack of training, lack of awareness, and interest of students and parents. Schools and teachers implement government policies to study from home as an effort to slow the spread of Covid-19 but at the same time ensure students are engaged in constructive activities through online learning. Various online media platforms are used in online learning, while teachers, students, and parents continue to make adjustments over time. However, the implementation of online learning has obstacles or constraints both from the aspect of human resources and infrastructure. Keywords: Strategy, Online Learning, Collaboration, Covid-19 Pandemic